Home-based music therapy for persons with dementia and their spouses as primary caregivers - Rosenbach, Michal; Dassa, Ayelet; Gilboa, Avi (Frontiers in Public Health, 2023)
Music therapy has been found to be an effective intervention for persons with dementia (PWD) and their primary caregivers (PC), yet the implementation of musical strategies to improve daily care in the home environment requires further exploration. This study developed and examined a home-based music therapy (HBMT) work model that offers weekly joint music therapy sessions, and additional bi-weekly phone-counseling sessions with the PC. This was followed by an additional 12-week support period that included 3 therapy sessions and 3 phone counseling sessions once every other fortnight, so that the same type of session occurred at a frequency of once a month. Participants were five couples (PWD + spouse as PC) who live in their home. Findings based on the qualitative multiple case study research method showed the importance of the music therapist’s (MT) continuous support. The MT’s presence made it possible to address the needs of both spouses, separately and together, while maintaining the required balance. Moreover, the MT’s presence enabled better implementation of the musical strategies independently and this was maintained during the intervention and the support period.